Does Livestock Ownership Affect Animal Source Foods Consumption and Child Nutritional Status? : Evidence from Rural Uganda - Azzarri, Carlo; Zezza, Alberto; Haile, Beliyou; Cross, Elizabeth (Taylor and Francis, 2015)
In many developing countries consumption of animal source foods (ASF) among the poor is still at a level where increasing its share in total caloric intake may have many positive nutritional benefits. This paper explores whether ownership of different livestock species increases consumption of ASF and helps improving child nutritional status, finding some evidence that both food consumption patterns and nutritional outcomes may be affected by livestock ownership in rural Uganda. Our results are suggestive that promoting (small) livestock ownership has the potential for affecting human nutrition in rural Uganda, but further research is needed to more precisely estimate the direction and size of these effects.